Incorporating Conditional Morality into Economic Decisions - David Masclet; David L. Dickinson (Institute of Labor Economics (IZA), 2019)
We present a framework that incorporates both moral motivations and fairness considerations into utility. The main idea is that individuals face a preference trade-off between their material individual interest and their desire to follow moral norms. In our model, we assume that moral motivation is conditional and may be influenced by others' actions. Specifically, in our framework moral obligation is a combination of two main components: an autonomous component and a social influence component that captures the influence of others. Our framework is able to explain many stylized results in the literature and to improve theories of economic behavior.
Keywords: B3; D6; D9; 330; fairness; ethical decision making; moral motivation; behavioral economics